Budgeting Costs and Returns for Central Florida Citrus Production, 2004-05 - Ronald P. Muraro; W. Chris Oswalt (EDIS, 2006)
FE629, a 34-page report by Ronald P. Muraro and W.C. Oswalt, is the 22nd year of the report. It is intended to be used for budgeting costs and returns by individual growers in Polk and Highland counties, though costs may be applicable to Hardee, Hillsborough, Lake and Orange Counties. Published by the UF Department of Food and Resource Economics, September 2005.